Enhancing Critical Thinking in Speaking through Problem-Based Learning: A Classroom Action Research - Sa'bandi, Aliffio; Sidabalok, Dameria Magdalena (Universitas PGRI Semarang, 2026)
This classroom action research investigated the effectiveness of Problem-Based Learning (PBL) in enhancing critical thinking skills within English speaking activities at Global Madani Senior High School. Conducted over two iterative cycles with 21 eleventh-grade students, the study employed a mixed-methods approach within a Classroom Action Research (CAR) framework. Quantitative data from pre- and post-tests, analyzed via a paired sample t-test, revealed a statistically significant improvement in students' critical speaking abilities, with the average score rising from 50.71 to 81.90 (p .001). Qualitative data from observations, recordings, and student journals illustrated a clear developmental trajectory: initial engagement in Cycle 1 exposed deficits in argument structure and logical reasoning, prompting the introduction of targeted scaffolds—including explicit argumentation frameworks and peer feedback protocols—in Cycle 2. The findings demonstrate that PBL’s efficacy is significantly amplified when integrated with responsive, reflective CAR cycles and structured linguistic-cognitive supports. The study concludes that embedding PBL within an adaptive CAR process fosters a synergistic environment where authentic problem-solving motivates communication, and deliberate scaffolding transforms engagement into disciplined, critical spoken discourse, offering a replicable model for enhancing higher-order thinking in EFL contexts.